Comprehensive pathological studies on Marek’s disease in HVT-1 vaccinated chickens flocks: Marek’s disease in HVT-1 vaccinated chickens - SHAILJA PANDEY; DEEPIKA LATHER; VIKAS NEHRA; GULSHAN NARANG (Indian Journal of Poultry Science, 2025)
Present study was conducted on poultry carcasses from HVT-1 vaccinated flocks received in the Department of Veterinary Pathology, LUVAS, Hisar for disease investigation. Pathological diagnosis revealed MD lesions in 9.7% cases, while Marek’s disease and lymphoid leucosis (MD+LL) mixed type lesions were observed in 1.5% cases mostly affecting more than 12-24 wks age groups of layer, broiler and dual purpose breeds. MDV was also confirmed in the tumour tissues by employing Real Time PCR techniques using Meq specific primer, while ALV infection was confirmed by conventional PCR. Grossly in MD affected chicken nodular growths of different sizes was evident which were white to pale yellow in colour and were observed in organs like lungs, heart, liver, kidney, spleen, proventriculus and ovaries However, brain, bursa of Fabricius, nerves and feather follicles did not reveal any enlargement or nodular growth. Infiltration and proliferation of neoplastic pleomorphic lymphoid cells were observed on histopathological examination of liver, spleen, lungs, intestine, kidney, ovary and proventriculus. Mixed infection (MD+LL) cases revealed islands of uniform neoplastic lymphoblasts cells in the parenchyma along with above lesions. Mean histopathological lesion score revealed severe involvement of liver, spleen and lungs. Overall mean percent histopathological lesion score was found maximum in dual purpose chicken i.e. 52.50% followed by layer (46.87%) and broiler (42.15%) breed. It may be concluded that MDV infection is still a problem in vaccinated layer and broiler breeder flocks in Haryana. The majority of neoplastic disease cases were detected in layer flocks with involvement of the liver, spleen, and lungs in the acute/visceral type of Marek’s disease; but the overall severity of lesions was more in dual purpose breed.